2014
DOI: 10.1093/jat/bku083
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Enzymatic Hydrolysis Using a Novel Recombinant β-Glucuronidase in Benzodiazepine Urinalysis

Abstract: Only trace amounts of parent benzodiazepines are present in urine following extensive metabolism and conjugation. Thus, hydrolysis of glucuronides is necessary for improved detection. Enzyme hydrolysis is preferred to retain identification specificity, but can be costly and time-consuming. The assessment of a novel recombinant β-glucuronidase for rapid hydrolysis in benzodiazepine urinalysis is presented. Glucuronide controls for oxazepam, lorazepam and temazepam were treated with IMCSzyme™ recombinant β-glucu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Then, 10 μL of each internal standard solution at 100 μg/mL was added to plasma. A total of 480 μL of β-glucuronidase enzyme, 10% v/v in sodium acetate (140 mM, pH 4.8) was added to plasma, which was vortexed and incubated for 16 h at 37 • C [32]. After incubation, 20 μL methanol was added to the sample, which was then centrifuged (3000× g; 5 min; 4 • C) before being applied to a pre-conditioned Bond Elut C18 500-mg cartridge (Alltech, Associates, Australia) and washed with 2 mL water: methanol: acetic acid solution (90:10:0.1).…”
Section: Preparation Of Plasma and Standardsmentioning
confidence: 97%
“…Then, 10 μL of each internal standard solution at 100 μg/mL was added to plasma. A total of 480 μL of β-glucuronidase enzyme, 10% v/v in sodium acetate (140 mM, pH 4.8) was added to plasma, which was vortexed and incubated for 16 h at 37 • C [32]. After incubation, 20 μL methanol was added to the sample, which was then centrifuged (3000× g; 5 min; 4 • C) before being applied to a pre-conditioned Bond Elut C18 500-mg cartridge (Alltech, Associates, Australia) and washed with 2 mL water: methanol: acetic acid solution (90:10:0.1).…”
Section: Preparation Of Plasma and Standardsmentioning
confidence: 97%
“…Results from several studies have concluded that parent drug recoveries for specific benzodiazepine drugs were increased, based on the incorporation of hydrolysis in sample preparation (16)(17)(18)(19)(20)(21)(22)(23). Hydrolysis reactions have been mediated by β-glucuronidase enzymes from abalone entrails, Helix pomatia (type H-3), Helix aspersa, Patella vulgata (type L-II), Escherichia coli, Chlamys opercularis, and bovine β-glucuronidase (16)(17)(18)(19)(20)(21)(22)(23). Some hydrolysis comparison studies have demonstrated that recombinant β-glucuronidase enzyme was more efficient than other enzyme sources by affording a rapid hydrolysis (5 min) at room temperature (16,17).…”
Section: Hydrolysis Of Benzodiazepine Drugsmentioning
confidence: 99%
“…Hydrolysis reactions have been mediated by β-glucuronidase enzymes from abalone entrails, Helix pomatia (type H-3), Helix aspersa, Patella vulgata (type L-II), Escherichia coli, Chlamys opercularis, and bovine β-glucuronidase (16)(17)(18)(19)(20)(21)(22)(23). Some hydrolysis comparison studies have demonstrated that recombinant β-glucuronidase enzyme was more efficient than other enzyme sources by affording a rapid hydrolysis (5 min) at room temperature (16,17). The recombinant source had a maximal hydrolysis recovery of >94% for oxazepam and lorazepam and >80% for temazepam (17).…”
Section: Hydrolysis Of Benzodiazepine Drugsmentioning
confidence: 99%
See 2 more Smart Citations